Determining the heat and mass exchange efficiency of a scraper heat exchanger for heating food semi-finished products - Zagorulko, Aleksey; Kasabova, Kateryna; Shevchenko, Anastasiia; Dmytrevskyi, Dmytro; Levchenko, Yuliia; Kalashnyk, Olena; Koshulko, Vitalii; Gromov, Aleksey (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is the process of heating fruit and berry purees made from apple, apricot, and honeysuckle. This paper reports an improved structure of a scraper heat exchanger for heating viscous liquid food products based on fruit and berry raw materials (purees, pastes). One of the main elements of the modernization is heating with a flexible film resistive electric heater of the radiant type instead of the conventional steam system, which has made it possible to eliminate steam fittings and reduce energy consumption. Additional equipment of the heat exchanger with a hinged blade with a remote plate enables turbulization of the product flow in the heat exchange zone, contributing to the formation of a stable film flow on the heating surface, which significantly improves the efficiency of heat transfer. The experimental and computational studies revealed the dependence of the heat transfer coefficient on raw material consumption and the frequency of rotation of the apparatus shaft. It was established that the heat transfer coefficient depends on the product flow rate and, after reaching the maximum (13…15) 10–3 kg/s, it decreases. The influence of rotor speed is less significant and is manifested mainly during the transition from 1.0 to 1.5 s⁻1. Comparative analysis revealed that the use of an improved blade with a remote plate makes it possible to increase the heat transfer coefficient by 1.2 times compared to the conventional design. Calculations of specific heat consumption showed its decrease from 250 to 222 kJ/kg, which is a saving of 12.5%. The proposed structural solutions make it possible to ensure the stability of temperature regimes, reduce energy consumption, improve the quality of heat treatment and process automation. This is especially important for the processing of heat-sensitive and dense products in the food industry